2012
DOI: 10.1212/wnl.0b013e3182516244
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of antidepressants in Parkinson disease

Abstract: This study provides Class I evidence that paroxetine and venlafaxine XR are effective in treating depression in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
210
4
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(230 citation statements)
references
References 34 publications
3
210
4
13
Order By: Relevance
“…In two randomized trials comparing bilateral STN DBS with best medical therapy at 6-month follow-up, results correspond to an improvement of 17% and 25% in both DBS series, with almost no change in the medication groups (23,24). In other studies improvement of up to 68% has been reported in PDQ-39 at up to 24 months of follow up (13,21,11,20). Interestingly, an improvement in QoL in pallidal and subthalamic DBS after 2 years in a randomized trial was only moderate and reached 11.2% and 8.9% respectively (7).…”
Section: Disclosurementioning
confidence: 78%
“…In two randomized trials comparing bilateral STN DBS with best medical therapy at 6-month follow-up, results correspond to an improvement of 17% and 25% in both DBS series, with almost no change in the medication groups (23,24). In other studies improvement of up to 68% has been reported in PDQ-39 at up to 24 months of follow up (13,21,11,20). Interestingly, an improvement in QoL in pallidal and subthalamic DBS after 2 years in a randomized trial was only moderate and reached 11.2% and 8.9% respectively (7).…”
Section: Disclosurementioning
confidence: 78%
“…Therefore, in most cases, MAO-B inhibitors can be safely administered along with SSRIs. This is important because the co-morbidity of depression and PD makes it quite likely that an SSRI will be required at some point during the disease course [43][44][45]. Discontinuing a MAO-B inhibitor in order to start an SSRI or using an alternative class of antidepressant to avoid interaction is generally not necessary as long as the recommended dose of MAO-B inhibitor is not exceeded.…”
Section: Safety Of Mao-b Inhibitorsmentioning
confidence: 99%
“…Paroxetine and Venlafaxine are both effective to decrease the depression in patients with Parkinson's disease. [46] Antipsychotics in Parkinson's disease: Psychosis, hallucination and confusion are common problems in patients with Parkinson's disease treated with long-term dopaminergic treatment. Clozapine, an atypical antipsychotic is effective to control drug-induced psychosis and tremor in Parkinson's disease [47].…”
Section: Antidepressant In Parkinson Diseasementioning
confidence: 99%